2014
DOI: 10.5847/wjem.j.issn.1920-8642.2014.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Changes in biological behaviors of rat dermal fibroblasts induced by high expression of MMP9

Abstract: BACKGROUND:The high level of matrix metalloproteinase 9 (MMP9) is thought to slow down the healing of diabetic foot ulcers. Whether it can influence the biological behaviors of skin fi broblasts and affect wound healing is still unclear. The present study aimed to observe changes in the biological behaviors of rat dermal fi broblasts induced by high expression of MMP9 and to clarify the possible mechanisms of wound healing for diabetic foot.METHODS: A cell model of skin fi broblast with high expression of MMP9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 9 publications
1
7
0
Order By: Relevance
“…18 Existing literature was used when selecting the specific concentrations to represent these conditions in the experiments. 8,19,20 Deveci et al 21 showed that a high-glucose concentration (35 mM) induced apoptosis in keratinocytes in vitro. Our results showed that in vitro both skin cell types were able to tolerate hyperglycemic conditions well (up to 26 mM), and fibroblasts cultured in slightly hyperglycemic concentration (10 mM) exhibited increased proliferation in comparison to lower glucose concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…18 Existing literature was used when selecting the specific concentrations to represent these conditions in the experiments. 8,19,20 Deveci et al 21 showed that a high-glucose concentration (35 mM) induced apoptosis in keratinocytes in vitro. Our results showed that in vitro both skin cell types were able to tolerate hyperglycemic conditions well (up to 26 mM), and fibroblasts cultured in slightly hyperglycemic concentration (10 mM) exhibited increased proliferation in comparison to lower glucose concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Also, FLS secrete collagenases and metalloproteases (MMP), such as MMP-9, that start degrading cartilage ECM after activation [108]. Other MMP involved are MMP-13 [109], MMP-1 [110], MMP-2 [111], and MMP-3.…”
Section: Metabolic Changes Deregulate Fls Phenotype After Activationmentioning
confidence: 99%
“…Several molecules and growth factors, such as PDGF, are essential for the formation of ECM-degrading invadosomal structures and cartilage invasion and activate several signaling pathways, including the PI3K/AKT pathway, known to be upstream of glucose metabolism [ 107 ]. Also, FLS secrete collagenases and metalloproteases (MMP), such as MMP-9, that start degrading cartilage ECM after activation [ 108 ]. Other MMP involved are MMP-13 [ 109 ], MMP-1 [ 110 ], MMP-2 [ 111 ], and MMP-3.…”
Section: Metabolic Changes Deregulate Fls Phenotype After Activationmentioning
confidence: 99%
“…PDGF is essential for the formation of hypertrophic FLS architecture and the extracellular matrix-degrading invadosome, invasion to cartilage, via activation of several signaling pathways, particularly the PI3K/AKT pathway [ 86 ]. Also, the intimal lining has been identified as the primary source of MMPs in RA, and is able to active FLSs with the secretion of collagenases and metalloproteinases, such as MMP-2 and MMP-9, and initiate the destruction of ECM and cartilage [ 87 , 88 ].…”
Section: The Transformed Phenotype Of Ra Flssmentioning
confidence: 99%